(untitled) (LEARNing Landscapes, 2016)
Incorporating the Arts into immersive place-based education programs can increase connectivity with the environment and facilitate the development of socially responsible and pro-environmental learners. Increasingly, children and adolescents are alienated and detached from the natural world. Given this noticeable shift, educators working in the outdoor setting need to rethink their modus operandi. Past attempts to promote learner connection with the environment have centred upon short-term stays and risk-centric approaches that embrace high adrenaline activities. This is the antithesis of Touched By The Earth, a yearlong place-based enrichment program using multi-modal creative methods with young learners to delve into the impact of experiential learning and how the Arts promote a personal relationship with the environment.